Community-based interventions to prevent stroke in low and middle-income countries: A systematic review - Iffat Nowrin; Jeenat Mehareen; Dipika Shankar Bhattacharyya; KM Saif-Ur-Rahman (Health Sciences Review, 2023)
We aimed to identify community-based interventions to prevent stroke in low-and-middle-income countries. A comprehensive search in Medline through PubMed, Web of Science (core collection), and Scopus was conducted in October, 2021 and updated in August, 2023. Studies published only in English between 1st January, 2000 and August 26, 2023 were included in the review. The screening and data extraction were performed by two reviewers independently. Two authors independently evaluated the included papers' Risk of Bias; we utilized the Cochrane ROB (Risk of Bias) tool for randomized controlled trials (RCT) and non-randomized studies were assessed using ROBANS (Risk of Bias Assessment tool for non-randomized studies). Meta-analysis was not conducted due to the heterogeneity of the included studies in terms of methods and outcomes. A narrative synthesis was performed to report the results. This systematic review was registered in PROSPERO (International prospective register of systematic reviews) – CRD 42021283670. A total of six studies were included in the review. Most of the studies highlighted community-based educational intervention to improve knowledge regarding stroke, it's signs, and risk factors. An important component of community-based intervention found in the review was involving community health professionals in educating the local population about health. Educational interventions were found effective in reducing stroke risk factors such as blood pressure, and cholesterol level. To lessen the enormous burden of stroke, effective community-based programs for prevention can be expanded and incorporated into resource-poor health systems.